Analisa Penerapan Akuntansi Lingkungan di RSUD Waru Kabupaten Pamekasan - Al Humaidi; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research was conducted with the aim of knowing the Application of Environmental Accounting at Waru Hospital, Pamekasan Regency. The sample used was the Sumbersuko Village group, Wagir District, Malang Regency. The types of data used are primary data and secondary data. Methods of data collection using interview techniques, direct observation and documentation. The data analysis method used is quantitative analysis. The first step is to reduce the data, then present the data and draw conclusions. The Waru Pamekasan Regional General Hospital (RSUD) is one of the Regional Apparatus Organizations (OPD) that serves public health in the north coast of Bumi Gerbang Salam. So it is quite appropriate to get a budget allocation from the 2021 Tobacco Products Excise Revenue Sharing Fund (DBHCHT). In 2021, the Pamekasan Regency Government will indeed receive a DBHCHT budget of IDR 64.5 billion which will be allocated for three main sectors. Namely for the welfare of the community, the field of law enforcement, and the health sector. One of them is in the health sector, finally it can be allocated for updating health services at the Waru Pamekasan Hospital.Keywords: Accounting treatment, waste processing cost